Development of preparatory grade children’s reading skills in Romania - Bianca BALEA; Maria KOVACS; Sorana POGĂCEAN (Revista de Știinţe Educaţiei)
Since 2012, when preparatory grade (PG) became compulsory in Romania for 6-year olds, little understanding has been gained of how children’s literacy evolves in PG, although over the same period, Romanian 15-year olds’ reading performance has shown no signs of improvement (Noveanu et al, 2023). Children enter school with broadly varying literacy skills depending on several factors. As their academic success is heavily dependent on their early reading, understanding how children’s literacy skills evolve in the early years of school is important for both educators and education policy-makers. This article explores the evolution of Romanian PG students’ six emergent literacy skills (ELS) and whether four selected factors influence this evolution (progress in ELS and ELS at the end of PG) significantly: ELS at the start of PG; previous attendance of preschool; school attendance frequency in PG; and socio-economic status. ELS were assessed for 2134 PG students at the beginning and at the end of the school year. A specific emergent literacy assessment instrument (Temple and Temple, 2023) was used yielding scores from 0 (minimum) to 150 (maximum). To measure the changes in six emergent literacy skills (ELS) over the course of the PG (Q1) and determine whether a selection of factors influence progress in ELS and final ELS (Q2), the present research design uses a pre- and post-evaluation approach. Descriptive and inferential statistics were employed. We found an average initial score of 40.5 points and a final average score of 117.9 points, with the average 77.4-point progress being significantly influenced by previous attendance of preschool and school attendance in PG, as well as ELS at the start of PG, but not SES. Children’s final scores were however influenced significantly by all four investigated factors.